A paradox view on green human resource management: insights from the Italian context. Issue 2 (19th January 2016) - Guerci, Marco; Carollo, Luca
Abstract : Paradox – understood as a set of contradictory and incompatible poles all supported by apparently sound arguments – is considered to be a key element in modern organizations. As a result, paradox scholars argue that successful managers are those able to accept the tensions arising from the paradox and able to pursue all its constitutive poles simultaneously instead of choosing only one of them. Paradox theory has been recently applied to corporate sustainability, and it is a theoretical approach that has been endorsed by influential authors also in the human resource management (HRM) field. In this context, this paper takes the still unexplored opportunity to apply paradox theory to green HRM. In particular, it explores the HRM-related paradoxes perceived by organizations developing environmental sustainability via HRM. Adopting a comparative multiple case study approach, semi-structured interviews and document analysis were conducted in six Italian companies explicitly pursuing an environmental strategy. The findings encompass the main characteristics of the green HRM systems of the organizations analyzed, and a list is provided of eight HRM-related paradoxes perceived by those organizations. For each paradox, we present and discuss its contrasting poles and the components of the HRM system that it affects. The implications of the findings for both green HRM research and practice are presented and discussed.